Ethnomathematics Exploration of Trigonometric Transformation Forms on Joget Lambak Pucuk Pisang at the Opening of the National Culture Week in 2020 - Mahardika, Nova Pitdianti (JMEA : Journal of Mathematics Education and Application, 2024)
Melayu dance is often performed by students at school events, but they often do not know that there are many mathematical elements in a Melayu dance. This encourages the author to try to find the application of geometry transformation contained in joget lambak dance. Many types of Melayu dances are very famous, one example is kapur sirih which is used to welcome special guests and joget lambak dance which has a special meaning, where the joget lambak dance on this occasion will be matched with the Melayu song "pucuk pisang". Joget lambak is a dance of young people, joget lambak trips are usually full of nuances of joy, nuances of cheerfulness, which when dancing also occur dancing interactions between young people in order to find a partner to release longing. Usually joget lambak dance becomes an intermediary for them to express that feeling. Geometric transformation is a transformation that studies the process of changing a geometric field that includes its own position, size, and shape, which is caused by translation, dilation, matrix-compatible transformation, rotation, reflection, scale change, and composition of two transformations. This research is a type of literature research with a qualitative approach. The data is collected by document study and analyzed by data analysis technique which is doing a documentation. The result of this study is that it turns out that the joget lambak dance is not only about art, but in it we can also use it as one of the lessons on geometry transformation material. There are so many forms of geometry transformation contained in the lambak dance movement pattern.